The distinctiveness of polyamory - Brunning, L (Wiley, 2018)
Polyamory is a form of consensual non-monogamy. To render it palatable to critics, activists and theorists often accentuate its similarity to monogamy. I argue that this strategy conceals the distinctive character of polyamorous intimacy. A more discriminating account of polyamory helps me answer objections to the lifestyle whilst noting some of its unique pitfalls. I define polyamory, and explain why people pursue this lifestyle. Many think polyamory is an inferior form of intimacy; I describe four of their main objections. I explain how commitment to ‘the polyamorous possibility’ prompts one to viscerally experience personal, practical, and social constraints. Unlike monogamous dynamics, these confrontations are mediated by third parties who destabilise the familiar dynamics of coupled life. Polyamory can be emotionally challenging but, as I outline in the article, it is sustained by interpersonal emotional work that helps people feel and understand their emotions, communicate without confrontation, and contain the difficult emotions of others. This work is qualitatively and quantitatively intensified in polyamory. Finally, I rebut objections to polyamory whilst also acknowledging the ways polyamory has its own pitfalls.